Analisis Konseling Behavioral dalam Mengatasi Kecemasan pada Remaja - Haikal Haikal; Ita Anita; Sabila Khaeriani Putri; Imalatul Khairat (Pusat Riset dan Inovasi Nasional, 2025)
This study is a descriptive qualitative literature review aimed at analyzing the application of systematic desensitization techniques within behavioral counseling as an intervention strategy to address anxiety in adolescents. Data were collected through a comprehensive review of relevant scientific literature, including academic journals, counseling psychology textbooks, and research articles. Systematic desensitization is identified as one of the most effective techniques in behavioral approaches, functioning by gradually exposing clients to anxiety-triggering stimuli while simultaneously teaching relaxation techniques. This therapeutic process enables adolescents to develop healthier and more adaptive behavioral responses when facing social situations or anxiety-inducing conditions. A thematic analysis was conducted to examine implementation strategies, contextual applications, and the technique’s effectiveness in transforming maladaptive behaviors. The findings indicate that systematic desensitization significantly reduces anxiety levels, enhances adolescents' self-confidence, and decreases avoidant behaviors that hinder social functioning. In addition to the intervention itself, therapeutic success is strongly influenced by supporting factors such as the empathetic relationship between counselor and client, social support involvement, and the client’s psychological readiness to change. With its structured and measurable procedures, this technique serves as a practical guideline in psychological counseling services, particularly for addressing adolescent anxiety in a focused and effective manner. This research is expected to provide both theoretical insights and practical guidance for counseling practitioners in developing behavior-based interventions for clients experiencing anxiety disorders.